Inter-individual Variability for High Fat Diet Consumption in Inbred C57BL/6 Mice - De Francesco, Pablo Nicolás (2019)
Since inbred C57BL/6 mice are known to show inter-individual phenotypic variability for some traits, we tested the hypothesis that inbred C57BL/6 mice display a different tendency to consume a high fat (HF) diet. For this purpose, we used a compilation of HF intake data from an experimental protocol in which satiated mice were exposed to a HF pellet every morning for 2-h over 4 consecutive days. We found that mice displayed a large degree of variability in HF intake. Since day 1 HF intake significantly correlated with HF intake in successive days, we applied a hierarchical clustering algorithm on HF intake measurements in days 2, 3, and 4 in order to classify mice into "low" or "high" HF intake groups. "Low" HF intake group showed a day 1 HF intake similar to that seen in mice exposed to regular chow, while "high" HF intake group showed a higher day 1 HF intake as compared to "low" HF intake group. Both groups of mice increased HF consumption over the successive days, but "high" HF intake group always displayed a higher HF consumption than the "low" HF intake group. As compared to "low" HF intake group, "high" HF intake group showed a higher number of dopamine neurons positive for c-Fos in the VTA after the last event of HF intake. Thus, inbred C57BL/6 mice show inter-individual variability for HF intake and such feature may be linked to a different response to the rewarding properties of the HF diet.